Chemical composition of the essential oil of Centaurea grinensis Reuter and Centaurea apiculata Ledeb: Growing wild in Croatia and Bulgaria, respectively and PCA analysis of subgenus Lopholoma (Cass.) Dobrocz. (2nd November 2017) - Riccobono, L.; Maggio, A.; Bruno, M.; Bancheva, S.; Santucci, O.; Senatore, F.
Abstract: In the present study, the chemical composition of the essential oils from aerial parts of Centaurea grinensis Reuter (K ) collected at Žuta Lova, near Senj (Croatia), and aerial parts (L1 ) and flowers (L2 ) of C. apiculata Ledeb. collected near Rebro village, near Breznik town, Znepole Region (Bulgaria), both belonging to subgenus Lopholoma (Cass.) Dobrocz, was evaluated by GC and GC-MS. The main components ofK were 4-vinyl guaiacol (21.5%), hexadecanoic acid (16.2%), acetophenone (12.5%). Caryophyllene oxide (15.8%) together with sphathulenol (14.5%) and humulene epoxide II (9.4%) were recognized as the main constituent of both the aerial part (L1 ) and flowers (L2 ) of C. apiculata . Furthermore, a complete review on the composition of the essential oils of all the Centaurea taxa belonging to subgenus Lopholoma studied so far has been inserted and cluster analysis (PCA) was carried out.